MENINGKATKAN DAYA SAING INDUSTRI PENGGILINGAN PADI MELALUI MEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Rosid, A.; Nusantoro, J.; ., Yateno (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana Mengabdi, 2022)
As the largest district in Lampung, Central Lampung has a vision of "Agribusiness Earth" that is Advanced, Safe, Prosperous, and Environmentally Friendly with Excellent Quality Public Service, each District must be able to make a regional development program in accordance with the potential of each region. In accordance with this vision, one of the areas that has great potential to be developed is Trimurjo District, also known as one of the rice barns in Central Lampung. That is why many rice mills operate in Trimurjo, especially in the villages of Pujokerto and Pujobasuki, not even a few have operated for decades, but unfortunately many rice mills are unable to survive facing industrial competition. That is why many rice mills operate in Trimurjo, especially in the villages of Pujokerto and Pujobasuki, not even a few have operated for decades, but unfortunately few rice mills are unable to survive facing industrial competition. One reason is the inability of companies to manage administration, finance and in the marketing sector. Therefore, through the 2018 KKN PPM Grant: the Muhammadiyah Metro University team is trying to create a solution for some of these problems including: : creation of financial statement applications for rice milling (SIMPADI), administrative accounting, and making rice packaging.   Keywords : Rice Milling, Application of Financial Statements, Industrial Competitiveness, Rice Packaging, Administrative Assistance